Does Pathological Complete Response after Neoadjuvant Therapy Influence Postoperative Morbidity in Rectal Cancer after Transanal Total Mesorectal Excision? - Svoboda, Martin; Procházka, Vladimír; Grolich, Tomáš; Pavlík, Tomáš; Mazalová, Monika; Kala, Zdeněk (Journal of gastrointestinal cancer, 2023)
PURPOSE: It is still unclear if pathological complete response (pCR) after neoadjuvant chemoradiotherapy (CRT) in patients treated for rectal cancer causes worse postoperative outcomes, especially after transanal total mesorectal excision (TaTME). Worse postoperative outcomes might be an argument for an organ preserving watch and wait strategy in fragile patients and patients with comorbidities. The aim of this study is to evaluate whether patients treated for rectal cancer who had pCR to neoadjuvant therapy develop worse postoperative outcomes after TaTME than patients without complete response. METHODS: Comparative retrospective analysis (with nearest neighbor matching algorithm) of postoperative outcomes in two groups of patients, with pCR, n = 15 and without pCR (non-pCR), n = 57. All patients were operated on only by one surgical approach, TaTME, for middle and distal rectal tumors. All procedures were performed by one surgical team between 2014 and 2020 at the University Hospital Brno in Czech Republic. RESULTS: Overall morbidity was comparable between the groups (pCR group - 53.8% vs. non-pCR - 38.6%, p = 0.381). Anastomotic leak (AL) was observed in 33.3% of patients with pCR and in 17.5% of patients in the non-pCR group without statistical significance (p = 0.281). CONCLUSION: In conclusion, pathological complete response after neoadjuvant therapy does not appear to affect postoperative morbidity in rectal cancer after TaTME. Therefore, in patients with complete response who are not adherent to W&W surveillance, surgical resection can be perform without increased postoperative complications.
Keywords: Neoadjuvant therapy; Transanal total mesorectal excision; neoadjuvantní terapie; Humans; laparoskopie; Pathological complete response; Postoperative outcomes; Rectum; morbidita; výsledek terapie; lidé; nádory rekta; Postoperative Complications; Anastomotic leak; pooperační komplikace; Rectal Neoplasms; Retrospective Studies; Morbidity; Treatment Outcome; Neoadjuvant Therapy; Laparoscopy; retrospektivní studie; rektum